CONCEITO DE MISSÃO EM JOHN STOTT E RENÉ PADILLA: RELAÇÃO ENTRE PROCLAMAÇÃO DA PALAVRA E AÇÃO SOCIAL - Silva, Marcos Aurélio da (2012)
The concept of Mission on John R. W. Stott and C. René Padilla is a research that analyses the relation between the proclamation of the word and the social action as contextualized in the Gospel. This thesis, developed towards the granting of the Master s Degree in Sciences of Religion, belongs to the Religion, Society and Culture research field. The bibliography revision was the methodology used for the data collection. The question that guided the research was: what is the concept of world mission in J. Stott and integral mission in R. Padilla? Among the answers it was possible to compare the theology of J. Stott and R. Padilla. In the first chapter, the concept of world mission in the theology of J. Stott was presented. In the second chapter, the concept of integral mission in the theology of R. Padilla was presented as well. In the third chapter, through a comparison it has been demonstrated that J. Stott emphasizes the proclamation of the word by the church, leaving the social service action as a second matter, because his priority is the need of salvation of the sinner, through repentance and the acceptance of Jesus Christ as the savior. On the other hand, R. Padilla sets the proclamation of the word and the service through social action in a joint way and making them inseparable in order to achieve the announcement of the Kingdom of God in society.